2022
DOI: 10.1111/mec.16619
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic plasticity of mixotrophic algae is key for their persistence in browning environments

Abstract: Light availability is the main regulator of primary production, shaping photosynthetic communities and their production of ecologically important biomolecules. In freshwater ecosystems, increasing dissolved organic carbon (DOC) concentrations, commonly known as browning, leads to lower light availability and the proliferation of mixotrophic phytoplankton. Here, a mixotrophic algal species (Cryptomonas sp.) was grown under five increasing DOC concentrations to uncover the plastic responses behind the success of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 60 publications
2
14
0
Order By: Relevance
“…This may explain why the dominant cyanobacterium Phillips et al, 2013). This suggests mixotrophy as the most plausible species trait accounting for the success of cryptophytes in the brown enclosures (Calderini et al, 2022;Grujcic et al, 2018;Hansson et al, 2019). Increasing dominance of mixotrophic phytoplankton under conditions of browning in stratified lakes has also been repeatedly reported by others (Bergström et al, 2003;Deininger et al, 2017;Wilken et al, 2018).…”
Section: Importance Of Underwater Light Conditions Induced By Browningsupporting
confidence: 52%
“…This may explain why the dominant cyanobacterium Phillips et al, 2013). This suggests mixotrophy as the most plausible species trait accounting for the success of cryptophytes in the brown enclosures (Calderini et al, 2022;Grujcic et al, 2018;Hansson et al, 2019). Increasing dominance of mixotrophic phytoplankton under conditions of browning in stratified lakes has also been repeatedly reported by others (Bergström et al, 2003;Deininger et al, 2017;Wilken et al, 2018).…”
Section: Importance Of Underwater Light Conditions Induced By Browningsupporting
confidence: 52%
“…Limitations of inorganic carbon and light may be overcome by utilizing terrestrial organic carbon (Calderini et al, 2022;Tittel et al, 2009). In addition to highly labile terrestrial carbohydrates, freshwater ecosystems also receive potentially recalcitrant organic carbon sources, for example lignocellulose, which forms 80 to 90% of terrestrial inputs to lakes and rivers (Brett et al, 2017;Jones, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…However, in these experiments, light has been available, and thus, it is uncertain whether the actual biosynthesis of essential biomolecules occurs only under light (autotrophy). Based on the previous literature (Glibert & Legrand, 2006), it seems that almost all phytoplankton species are capable of osmotrophy and thus could utilize terrestrial dissolved organic carbon (DOC) (Tittel et al, 2009) or plastic leachates (Sheridan et al, 2022), and thus could integrate autochthonous, allochthonous and anthropogenic carbon sources in aquatic food webs (Calderini et al, 2022;Granéli et al, 1999;Selosse et al, 2017;Tittel et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Combining autotrophic and heterotrophic mechanisms might enable phytoplankton to maintain growth, especially under highly variable and partially stressful conditions such as light limitation, which is common in estuaries and similar habitats (20). Different studies have found mixotrophy to be associated with reduced light availability, which has largely been investigated for phagotrophs (9,23) and benthic diatoms (24). Some phytoplankton taxa have been shown to even survive complete darkness on the basis of organic carbon (4,25).…”
Section: Organic Carbon Acquisition Is Not Primarily a Strategy To De...mentioning
confidence: 99%
“…The utilisation of organic compounds in such ecosystems might be critical for phytoplankton to maintain growth, especially where light is limited as a consequence of high loads of suspended matter. Different phytoplankton taxa have been shown to survive and grow based on organic carbon in the dark and at reduced light levels (4,9,2325). Hence, unsurprisingly, the importance of mixotrophic taxa in estuarine ecosystems has been reported in several studies (2629).…”
Section: Introductionmentioning
confidence: 99%